Of Monsters and Men: Religious Conflict, Radicalism, and Sexual Exceptionalism in the Works of John Chrysostom - De Wet, Chris L. (Journal of early Christian history, 2016)
The purpose of this article is to investigate the dynamics between religious conflict and sexual exceptionalism, as a means to radicalise members of a religious group, in the works of John Chrysostom (347-407 AD). Using modern terms, Chrysostom aims to infiltrate and minimise the ‘grey zone’ of religious identity and participation by constructing the sexual identity of the group he represents as masculine, pure, and dominant, and that of his opponents as inferior, perverse, and diseased. Chrysostom affirms the sexual exceptionalism of his radical adherents by means of inclusion - it is no longer one’s ethnicity, gender, class, or social status that are markers of exceptionality, but rather the presence of self-mastery and chastity, or sōphrosynē. Chrysostom abnormalises his opponents by means of teratogenisation, that is by making monsters out of them, in highlighting their abnormal pathic excess, corporeal mutilation, demonisation, psychic disease, and puerility. The masculinity of the radicals is affirmed and the sexual inferiority of the opponents sketched in vivid detail. By means of this case study from Chrysostom, the article hopes to emphasise the importance of gender and sexuality in the study of religious conflict past and present.